Residential urban food environment profiles and diet outcomes among adults in Brooklyn, New York: a cross-sectional study. Issue 4 (17th April 2023) - Figueroa, Roger; Baker, Katherine; Capellan, Joel; Pinheiro, Laura C; Burd, Laura; Lim, Jane; Chiong, Reah; Eboh, Relicious; Phillips, Erica
Abstract: Objective: To assess the clustering properties of residential urban food environment indicators across neighbourhoods and to determine if clustering profiles are associated with diet outcomes among adults in Brooklyn, New York. Design: Cross-sectional. Setting: Five neighbourhoods in Brooklyn, New York. Participants: Survey data ( n 1493) were collected among adults in Brooklyn, New York between April 2019 and September 2019. Data for food environment indicators (fast-food restaurants, bodegas, supermarkets, farmer's markets, community kitchens, Supplemental Nutrition Assistance Program application centres, food pantries) were drawn from New York databases. Latent profile analysis (LPA) was used to identify individuals' food access-related profiles, based on food environments measured by the availability of each outlet within each participant's 800-m buffer. Profile memberships were associated with dietary outcomes using mixed linear regression. Results: LPA identified four residential urban food environment profiles (with significant high clusters ranging from 17 to 57 across profiles): limited/low food access, ( n 587), bodega-dense ( n 140), food swamp ( n 254) and high food access ( n 512) profiles. Diet outcomes were not statistically different across identified profiles. Only participants in the limited/low food access profile were more likely to consume sugar-sweetened beverages (SSB) than those in the bodega-dense profile (b = 0·44, P < 0·05) in adjusted models. Conclusions: Individuals in limited and low food access neighbourhoods are vulnerable to consuming significant amounts of SSB compared with those in bodega-dense communities. Further research is warranted to elucidate strategies to improve fruit and vegetable consumption while reducing SSB intake within residential urban food environments.